2018
DOI: 10.1111/jace.16136
|View full text |Cite
|
Sign up to set email alerts
|

Design on improving piezoelectric strain and temperature stability of KNN‐based ceramics

Abstract: Lead-free 0.99(0.96K 0.46 Na 0.54 Nb 1-x Ta x O 3 -0.04Bi 0.5 (Na 0.82 K 0.18 ) 0.5 ZrO 3 )-0.01CaZrO 3 (0.99(0.96KNNTax-0.04BNZ)-0.01CZ) ceramics were prepared by a solid-state sintering method. Ta 2 O 5 doped in the 0.99(0.96KNNTax-0.04BNZ)-0.01CZ ceramics results in a phase structure transition from the orthorhombic (O)/tetragonal (T) phase to the rhombohedral (R)/T phase. The Ta 2 O 5 dopant induces a decrease in the average grain size from~1.70 to~0.69 μm. At x = 0.02 and 0.04, the ceramics have a high re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…24,25 More importantly, other groups not only constructed the NPB successfully, but also achieved enhanced performance (including d 33 values and strain temperature stability). 73,86,212,[221][222][223][224][225][226][227][228] For example, Zhang et al successfully constructed the NPB and even obtained higher d 33 values (e.g., 512 pC N À1 ) than our previously reported ones (e.g., 419-450 pC N À1 ), using the same additives (e.g., Sb 5+ , (Bi 0.5 Na 0.5 )ZrO 3 and (Bi 0.5 Na 0.5 )HfO 3 ), as marked by the red dashed line. 45,54,68,69,104 [221][222][223]226,227 More interestingly, Zhai et al achieved an ultra-high d 33 value of 700 pC N À1 in highly textured KNN-3T ceramics.…”
Section: Validity and Scope Of The Npbmentioning
confidence: 99%
“…24,25 More importantly, other groups not only constructed the NPB successfully, but also achieved enhanced performance (including d 33 values and strain temperature stability). 73,86,212,[221][222][223][224][225][226][227][228] For example, Zhang et al successfully constructed the NPB and even obtained higher d 33 values (e.g., 512 pC N À1 ) than our previously reported ones (e.g., 419-450 pC N À1 ), using the same additives (e.g., Sb 5+ , (Bi 0.5 Na 0.5 )ZrO 3 and (Bi 0.5 Na 0.5 )HfO 3 ), as marked by the red dashed line. 45,54,68,69,104 [221][222][223]226,227 More interestingly, Zhai et al achieved an ultra-high d 33 value of 700 pC N À1 in highly textured KNN-3T ceramics.…”
Section: Validity and Scope Of The Npbmentioning
confidence: 99%
“…19,20 When 0.035 ⩽ x ⩽ 0.05, the I(002):I(200) = 1:2 at this case, combined with the dielectric temperature spectrum curve at low temperature, it can be judged that the ceramics formed a coexistence structure of R(R3m) phase and T(P4mm) phase. [21][22][23] As shown in Fig. 1c for the KNNS-x(BLZ-SS) ceramics sample at 10 kHz frequency in the temperature range of −150 °C-100 °C dielectric temperature spectrum, when x = 0, there is an anomalous peak in the dielectric temperature curve corresponding to the T R-O = −78 ℃.…”
Section: Resultsmentioning
confidence: 91%
“…[25][26][27] According to several investigations, Mn 4+ acts as a donor dopant and improves piezoelectric and ferroelectric behaviors. [28][29][30] A recent study found that adding 0.25 mol% MnO 2 to lead-free Bi 0.5 Na 0.5 TiO 3 -Bi 0.5 K 0.5 TiO 3 -BaTiO 3 piezoelectric ceramics increased their d 33 performance by 40%. 31 Parallel to this, Huajun, et al reported that doping MnO 2 improved the d 33 and electromechanical properties of Ba 0.98 Ca 0.02 Zr 0.02 Ti 0.98 O 3 .…”
Section: Introductionmentioning
confidence: 99%